FINANCIAL TRANSFORMATION IN THE DIGITAL ERA: STRATEGY AND IMPLEMENTATION OF MODERN FINANCIAL MANAGEMENT INENTREPRENEURSHIP - Thomas Kartomo; Heri Rismayanto; Samudra Syarif Wahyu Hidayatullah; Zakhi Bailatul Nur Avian; Kasmin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study explores the digital financial transformation and its impact on modern financial management strategies and implementation within entrepreneurship. As digital technologies such as real-time financial analytics, big data, and blockchain gain prominence, entrepreneurs are presented with tools that enhance financial management efficiency, improve decision-making, and enable faster responses to market changes. Digital transformation offers small and medium enterprises (SMEs) previously inaccessible access to financial data, which supports the creation of data- driven strategies. However, this transformation demands that entrepreneurs possess sophisticated skills in data analysis and financial literacy to leverage digital financial tools effectively. This study identifies key challenges such as the need for comprehensive digital literacy, data privacy and security risks, and high implementation costs that may limit the reach of digital transformation among SMEs. Although blockchain technology can increase transaction transparency and accountability, it remains underutilized by smaller businesses due to cost and regulatory concerns. Nevertheless, the findings indicate that gradual implementation and targeted adoption of digital tools can reduce risks and support sustainable transformation. This study suggests that entrepreneurs should adopt a phased approach to digital financial management, starting with automating basic processes to balance benefits with manageable risks. Ultimately, digital financial transformation not only enhances profitability and operational efficiency but also influences business structures, fosters transparency, and establishes trust with stakeholders. In a broader context, this transformation contributes to shaping a more adaptive and innovation-driven entrepreneurial ecosystem. By integrating strategic digital financial management practices, entrepreneurs can leverage the transformative potential of technology to achieve long-term growth and competitiveness in the digital era